Specific Primer Design of Leucine Rich Repeats and Guanylate Kinase Domain Containing (LRGUK) Genes in Type II Diabetes Mellitus Patients - Mushlih, Miftahul; Tis’iyyah , Siti Nur Maghfiroh; Rini, Chylen Setiyo; Sari, Azizah Krismonita (Universitas Nahdlatul Ulama Surabaya, 2022)
Diabetes Mellitus type II (DT2) is a disorder of insulin function (insulin resistance) caused by 2 factors, i.e. environmental and genetic factors. Previous studies have identified the presence of specific alleles that differentiate between DT2 and non-DT2 sufferers. Identification of the allele indicated leucine rich repeats and guanylate kinase domain containing (LRGUK) gene. The aim of this research was to design a specific primer to amplify LRGUK gene. The primer design was based on a 576 bp nucleotide base and added 100 bp in the 5' and 100 bp in the 3' direction using NCBI-Primer BLAST. The primers produced were selected based on eight criteria’s. The results were validated with 6 samples of DT2 patients and visualized using agarose gel. The results of the analysis showed that the primers Forward 5'-TCCTACTCTGTGTCCTTCCTTG-3' and Reverse 5'-GTGGTGACAAGGAGG TTTGC-3' were able to amplify specifically with a length of 687 bp.